Stage IV ovarian cancer: a retrospective study on patient's management and outcome in a single institution. Issue 4 (1st June 2005) - Brunisholz, Y.; Miller, J.; Proietto, A.
Abstract : The management of stage IV epithelial ovarian carcinoma remains controversial. The aim of this study was to evaluate and compare our results to other published series. A retrospective database and casenote review was performed on all patients diagnosed with stage IV disease over a ten-year period (1992–2002). Survival analysis was performed using the Kaplan–Meier and Mantel–Haenszel methods. The study group comprised 23 women. Nine had positive pleural effusions (39.1%), and 14 had other sites of metastases (60.9%). Nine patients underwent interval debulking (39.1%), and 14 were operated on primarily (60.9%). We had six postoperative complications (26.1%) but no perioperative deaths. Optimal cytoreduction (inferior or equal to 2 cm residual disease) was obtained in 18 patients (78.3%). The overall median survival was 22.6 months. There was no statistically significant difference in overall or disease-free survival between primary surgery and interval debulking. Patients with positive pleural effusions had significantly reduced survival compared to those with distant metastases in other sites. Interestingly, there was no difference in survival between optimally and suboptimally cytoreduced patients. Debulking surgery can be performed in patients with stage IV ovarian cancer, with an acceptable level of morbidity. Optimal cytoreduction is achievable in the majority of these patients. Interval debulking should be considered in selected patients